The Role of Neuroscience and Artificial Intelligence in Biophilic Architectural Design Based on the Principle of Symbiosis - Adityo, Adityo (Universitas Atma Jaya Yogyakarta, 2024)
Biophilic architecture aims to create an environment that enhances connectivity between humans and nature to improve physical, mental, and emotional well-being. This review analyses 25 recent scientific journals on the application of neuroscience and artificial intelligence (AI) to optimise biophilic architectural design based on the principle of symbiosis. Results show that neuroscience provides valuable insights into human psychophysiological responses to various biophilic elements, while AI enables complex data processing, predictive modelling, and real-time design adaptation. The collaboration of neuroscience and AI can help produce a more effective, responsive to human needs, and sustainable biophilic environment. On the other hand, flexibility is demonstrated by the breadth of the architectural design process phases that can be reached through this collaboration. However, methodological and ethical challenges must be addressed to ensure responsible application.